The Differences of Academic College Student’s Achievement Between Literation Field Class from High School and Man Students on English Education at Faculty of Tarbiyah and Teachers Training of State Islamic University of North Sumatra - Daulay, Ernita; Rafida, Tien (Budapest International Research and Critics University, 2018)
This research describes the context of learning or lectures at academic achievement colleges known as achievement indexes (IP) and cumulative grade index (GPA). This is confirmed in the process standard operation (SOP) of Lectures and Curriculum with the number Un-11.JSOPP-04-02.R0 published by the North Sumatra State Islamic University Medan that Academic achievement is the result achieved by student guidance in study activities at the University North Sumatra State Islamic Medan as proof of the success that has been achieved after conducting learning or lecture activities. The results achieved by these students can take the form of subject values, Grade Point Average (GPA), championship rank, graduation grade, and completing studies on time. In the perspective of the study of academic achievement theory known as learning outcomes. The discussion of learning outcomes cannot be separated from the study of the concept of learning itself, because learning outcomes are obtained after going through the learning process carried out by students. This research carried out using a mixed method approach, which is a combination of qualitative and quantitative research. Qualitative research used is naturalistic, because it is based on the consideration that what is sought in this research is data that will describe and paint complex social reality in such a way that it becomes a concrete social phenomenon. The research situation chosen in this study was the academic achievement of students from high school and aliyah madrasa in the English Education Study Program at the Faculty of Tarbiyah and Teacher Training at North Sumatra State Islamic University Medan, covering a broad context, involving many actors, time different places, different processes and processes